Non-linear models of species' responses to environmental and spatial gradients - Anderson MJ; Walsh DCI; Sweatman WL; Punnett AJ (John Wiley and Sons Ltd, 2022)
Species' responses to broad-scale environmental or spatial gradients are typically unimodal. Current models of species' responses along gradients tend to be overly simplistic (e.g., linear, quadratic or Gaussian GLMs), or are suitably flexible (e.g., splines, GAMs) but lack direct ecologically interpretable parameters. We describe a parametric framework for species-environment non-linear modelling (‘senlm’). The framework has two components: (i) a non-linear parametric mathematical function to model the mean species response along a gradient that allows asymmetry, flattening/peakedness or bimodality; and (ii) a statistical error distribution tailored for ecological data types, allowing intrinsic mean–variance relationships and zero-inflation. We demonstrate the utility of this model framework, highlighting the flexibility of a range of possible mean functions and a broad range of potential error distributions, in analyses of fish species' abundances along a depth gradient, and how they change over time and at different latitudes.
Keywords: abundance; biomass; counts; cover; ecological statistics; environmental variables; gradient analysis; latitude; species distribution models; zero-inflation; Animals; Nonlinear Dynamics; Environment; Spatial Analysis; Fishes